Macroeconomic and Demographic Drivers of Halal Product Exports in ASEAN Countries: A Panel Data Analysis of the Emerging Halal Trade Landscape - Rika Sugiarti; Maulana Syarif, Hidayatullah; Nur Azifah; Muhamad Rizky Rizaldy (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2026)
Purpose: This study aims to analyze the influence of macroeconomic indicators, foreign investment, and demographic factors on the export of halal products among ASEAN countries, namely Indonesia, Malaysia, Brunei Darussalam, Thailand, Singapore, the Philippines, Vietnam, Laos, Cambodia, and Myanmar during the period 2014–2023. Design/Methodology/Approach: This research employs a quantitative approach using panel data regression analysis. Model selection was conducted through the Chow test, Hausman test, and Lagrange Multiplier test, with the results indicating that the most appropriate model is the Fixed Effect Model (FEM). Findings: The study reveals that the Real Effective Exchange Rate (REER) and population growth exert a significant positive impact on ASEAN halal product exports. Conversely, Foreign Direct Investment (FDI) demonstrates a significant negative effect, while Gross Domestic Product (GDP) does not show a statistically significant partial influence. Collectively, all independent variables have a significant joint effect on halal product exports. Practical Implications: This study is expected to offer valuable implications for governments and policymakers across ASEAN in formulating strategies that support the region’s halal export development. Originality/Value: This research contributes to Halal Product Industry by highlighting macroeconomic indicators and demographic factors on the export of halal products among ASEAN countries.